2010
DOI: 10.2298/jsc090901096a
|View full text |Cite
|
Sign up to set email alerts
|

Acetic acid-promoted condensation of o-phenylenediamine with aldehydes into 2-aryl-1-(arylmethyl)-1H-benzimidazoles under microwave irradiation

Abstract: An efficient and simple procedure was developed for the green synthesis of various 2-aryl-1-(arylmethyl)-1H-benzimidazoles in high yields by acetic acid-promoted condensation of o-phenylenediamine with aldehydes in air under microwave irradiation and transition metal catalyst-free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…[37][38][39] However, we preferred hydrogen peroxide as oxidant over other available oxidizing agents since it is cheap, operationally safe, environmentally friendly, easy to handle and produces only water as a by product, which reduces purification requirements. [40][41][42][43] The HI is highly toxic and corrosive as harmful as molecular iodine to the environment.…”
Section: Resultsmentioning
confidence: 99%
“…[37][38][39] However, we preferred hydrogen peroxide as oxidant over other available oxidizing agents since it is cheap, operationally safe, environmentally friendly, easy to handle and produces only water as a by product, which reduces purification requirements. [40][41][42][43] The HI is highly toxic and corrosive as harmful as molecular iodine to the environment.…”
Section: Resultsmentioning
confidence: 99%
“…All of the synthesized compounds were characterized by their physical constant, comparison with authentic samples, IR, 1 H NMR, 13 C NMR spectroscopy, and elemental analysis. All of synthesized compounds are known as described by [34]. 13…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that a gentle manipulated method, eco-friendly and green aspects avoiding hazardous solvents, shorter reaction times and high yields of the products are the advantages of this method [35]. condition via oxidation of carbon-nitrogen bond which is a green, mild and inexpensive method [36]. acid/HCl confirming the use of a simple condensation method and ring-closing agents for the synthesis of 2-substituted benzimidazoles [37].…”
Section: Green Synthesis Of Benzimidazolementioning
confidence: 99%